2022
DOI: 10.3390/cells11152337
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Triad Alliance: Bile Acid, Taurine and Microbiota

Abstract: Taurine is the most abundant free amino acid in the body, and is mainly derived from the diet, but can also be produced endogenously from cysteine. It plays multiple essential roles in the body, including development, energy production, osmoregulation, prevention of oxidative stress, and inflammation. Taurine is also crucial as a molecule used to conjugate bile acids (BAs). In the gastrointestinal tract, BAs deconjugation by enteric bacteria results in high levels of unconjugated BAs and free taurine. Dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 428 publications
1
13
0
Order By: Relevance
“…[31] Studies show that taurine regulates the central nervous system function and modulates the intestinal micro-ecology. [32][33][34] Consistently, our study identified that taurine is abnormally accumulated in FS children, indicating its potential clinical value in FS treatment. Additionally, arginine has been documented to induce gut microbiota remodeling, which is closely related to brain development and function.…”
Section: Discussionsupporting
confidence: 82%
“…[31] Studies show that taurine regulates the central nervous system function and modulates the intestinal micro-ecology. [32][33][34] Consistently, our study identified that taurine is abnormally accumulated in FS children, indicating its potential clinical value in FS treatment. Additionally, arginine has been documented to induce gut microbiota remodeling, which is closely related to brain development and function.…”
Section: Discussionsupporting
confidence: 82%
“…The major sources of taurine are endogenous synthesis and diet. The liver has been reported to be the main site of taurine biosynthesis, with two distinct pathways in which cysteine dioxygenase (CDO) and cysteine sulfate decarboxylase (CSAD) play important roles [ 2 , 3 ]. Since the vast majority of organisms have a low capacity for taurine biosynthesis, the level of taurine in the body is maintained by dietary intake and, consequently, the circulating level of taurine is significantly affected by diet [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, taurine and indoleacetic acid showed downregulation outcomes when inulin was treated in this study. Taurine feeding has been reported to reduce fat accumulation and synthesis (Duszka, 2022; Lu et al., 2019), whereas indoleacetic acid is also related to lipid synthesis (Zhao et al., 2019). Taken together, these findings suggest that inulin may be involved in decreased energy metabolism in tapirs.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotic supplementation has shown to reduce waking cortisol and increase vigilance on emotional stimuli in human (Schmidt et al., 2015). Moreover, recent evidences have suggested that taurine also involved in the modulation of nerve system (Duszka, 2022). Overall, inulin as a potential key regulator of gut–brain pathway may affect the neuroendocrine metabolism in tapir.…”
Section: Discussionmentioning
confidence: 99%